The role of intelligent machines on the future battlefield, circa 2030 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Defence and Strategic Studies at Massey University, Palmerston North, New Zealand - Morton, Ben Robert (Massey University, 2009)
The application of Intelligent Machine (IM) technology to the battlefield in future has the potential to revolutionise warfare. Converging trends and incentives are propelling this technology towards military applications at an ever increasing rate. This thesis examines the state of IM employment on the battlefield at the year 2030. The methodology employed in undertaking this thesis is the Extrapolation method. It has been utilised to extrapolate a range of technological, social, geo-strategic and military trends, in order to determine the state of affairs regarding intelligent machines at the subject year 2030. Chapter One examines what proportion of modern military ground forces will consist of IMs at the subject year. It assesses factors both driving and obstructing the development and employment of IM technology, and compares these against environmental developments with respect to time. Chapter Two addresses the likely roles in which IMs will be employed on the battlefield. These include present day military functions, as well as possible new roles enabled by specific characteristics of IMs. The chapter also assesses the potential forms that these IMs may take. Chapter Three focuses on the level of autonomy to be granted to battlefield IMs. It analyses the risks and benefits of autonomous control, and also the advantages and disadvantages of the alternative of teleoperation. The level of autonomy will be a defining factor of the IM presence on the battlefield. Chapter Four investigates the potential organisational architectures that may be employed in organising, commanding and controlling IMs. Specifically, centralised, decentralised, and swarm organisation are examined. The advantages and disadvantages of each, as well as necessary enablers are considered in turn. The conclusion provides an aggregated picture of the IM battlefield presence at the year 2030. It surmises the predicted proportion, roles, the level of autonomy, and organisational architecture of IM technology on the battlefield at the subject year of 2030.
Keywords: Military technology; Artificial intelligence; Fields of Research::360000 Policy and Political Science::360200 Policy and Administration::360204 Defence studies